A network analysis of the relationship between perceived social support, emotion regulation, and job burnout among elementary and middle school teachers - Li, Yueyao; Nie, Yuyang; Ma, Zhaoming; Liu, Cong; Cao, Yuxian; Qu, Guofeng; Hou, Lijia; Du, Kangli; Guo, MingMing; Wang, Tianci; Zhu, Xilai (Frontiers in Psychology, 2025)
BackgroundJob burnout is a common mental health problem among primary and secondary school teacher populations, and navigating perceived social support and emotion regulation are recognized as important protective factors. The aim of this study was to explore the relationship between perceived social support, emotion regulation, and job burnout among elementary and secondary school teachers and to provide an in-depth analysis using network analysis and mediation modeling.MethodsA questionnaire was administered to 351 elementary and middle school teachers using the perceived social support Scale, Emotion Regulation Scale and Job Burnout Scale. Network analysis was used to depict the network of associations between the variables, and mediation analysis was used to test the mediating role of emotion regulation between perceived social support and Job Burnout.ResultsThe results of the network analysis revealed that the connections within variables were stronger than those across variables. The core associations between different dimensions included: “family support” and “emotional exhaustion,” “family support” and “depersonalization,” as well as “cognitive reappraisal” and “reduced personal accomplishment.” Family support exhibited the highest Bridging Expected Influence (BEI), is the core hub of the network. The mediation model confirmed the mediating role of emotion regulation, indicating that perceived social support indirectly affects job burnout through emotion regulation. In addition, there were no significant differences in network characteristics between genders or across school stages (elementary vs. middle school).ConclusionElementary and middle school teachers’ perceptions of perceived social support, emotion regulation, and job burnout constitute a dynamic network of associations, with family support and cognitive reappraisal as the core nodes, and emotion regulation mediating the role of perceived social support in alleviating job burnout. The study provides a theoretical basis and intervention target for improving teachers’ mental health by strengthening family support and cognitive reappraisal.